A companion to creative writing - Harper, Graeme (Chichester, Sussex, UK ; Malden, MA : Wiley-Blackwell is an imprint of John Wiley & Sons, 2013)
Covers the writing of poetry, fiction, new media, plays, films, radio works, and other literary genres and forms.
pt. I. Creative writing -- pt. II. The creative writer's profession -- pt. III. Creative writing in the world.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Creative writing -- Handbooks, manuals, etc; Authorship -- Handbooks, manuals, etc; English language -- Rhetoric -- Handbooks, manuals, etc; English language -- Composition and exercises -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; Authorship; Creative writing; English language -- Composition and exercises; English language -- Rhetoric; Electronic books; Handbooks and manuals